On the problem of the terminological-conceptual equivalence between two language and culture communities: the so called “differences in the matter” / Zum Problem der terminologisch-konzeptuellen Äquivalenz zwischen zwei Sprach- und Kulturgemeinschaften - Drößiger, Hans-Harry (Kalbotyra, 2007)
The article discusses issues concerning terminological-conceptual equivalence between so called “systems of concepts” of two language and culture communities in the context of the work of a translator or the translatability of terminologies. Based on several studies (mostly concerning legal terminology) carried out in the last few years in MA papers of students of the study program Interpreting/Translation of Vilnius University some of the general questions of terminology work can be pointed out that are connected to the problem of the so called terminological “gap” and need to be reassessed. On the basis of the studies concerning the language combination German-Lithuanian not only “pure” linguistic differences between those two languages but also “differences in the matter” (i.e. differences between the language and culture communities) always were identifiable. The examples presented in this article should demonstrate how those gaps in “systems of concepts” can be dealt with so that it can be useful in the work of an interpreter or a translator who stands between those two languages and cultures.